Analysis of optimal crosslink density and platelet size insensitivity in graphene-based artificial nacres. Issue 2 (22nd November 2017) - Wu, Kaijin; Song, Zhaoqiang; He, Linghui; Ni, Yong
Abstract : We analyzed the optimal crosslink density and platelet size insensitivity reported in graphene-based artificial nacres through a hybrid model. Abstract : Exploration of graphene-based artificial nacres with excellent mechanical properties demonstrates the potential to surpass natural nacre. Recent experimental studies report that optimal crosslink density defined as concentration of the surface functional groups is usually observed in these artificial nacres towards superb mechanical performance. A hybrid model integrating a nonlinear shear-lag model and atomistic simulations reveals the emergence of an optimal crosslink density at which the maximum strength and toughness are achieved. The origin is due to the balance among the reduction of in-plane tensile properties of the graphene sheets, the enhancement of the shear strength of the interlayer and the reduction of interface plasticity. In addition, our results also reveal that the size insensitivity of the graphene sheet appears when the shear stress of the interlayer is highly localized, the increase of the crosslink density intensifies the nonuniformity of the shear stress and the optimal mechanical properties of the artificial nacre cannot be further enhanced by tuning the size of the graphene sheets. Three kinds of interface molecular interactions with their optimal crosslink densities are also proposed to simultaneously maximize the strength and toughness of graphene-based artificial nacres.